1997
DOI: 10.1002/(sici)1096-8628(19971231)73:4<416::aid-ajmg9>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

HDR syndrome (hypoparathyroidism, sensorineural deafness, renal dysplasia) associated with del(10)(p13)

Abstract: A combination of hypoparathyroidism, sensorineural deafness, and renal dysplasia has been considered to be a new syndrome inherited in an autosomal dominant fashion; we name the condition "HDR syndrome." We describe a Japanese girl who has HDR syndrome associated with de novo del(10)(p13). The chromosome deletion suggests that the putative gene(s) responsible for HDR syndrome is located at a 10pter-->p13 region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 14 publications
1
72
1
3
Order By: Relevance
“…The sensorineural hearing loss in HDR patients can be both symmetric or asymmetric, and as tested by auditory brainstem response (ABR), conditioned orientation reflex tests or pure tone audiometry, it ranges in level from 40 dB to 105 dB (Bilous et al, 1992;Fujimoto et al, 1999;Hasegawa et al, 1997;Lichtner et al, 2000;Muroya et al, 2001). Although it is clear that hearing loss in HDR is usually somewhat more severe at the higher end of the frequency spectrum Muroya et al, 2001), no systematic audiometric evaluation has yet been made, and the exact pathophysiological mechanism causing the hearing defect remains largely unknown.…”
Section: Introductionmentioning
confidence: 65%
“…The sensorineural hearing loss in HDR patients can be both symmetric or asymmetric, and as tested by auditory brainstem response (ABR), conditioned orientation reflex tests or pure tone audiometry, it ranges in level from 40 dB to 105 dB (Bilous et al, 1992;Fujimoto et al, 1999;Hasegawa et al, 1997;Lichtner et al, 2000;Muroya et al, 2001). Although it is clear that hearing loss in HDR is usually somewhat more severe at the higher end of the frequency spectrum Muroya et al, 2001), no systematic audiometric evaluation has yet been made, and the exact pathophysiological mechanism causing the hearing defect remains largely unknown.…”
Section: Introductionmentioning
confidence: 65%
“…To date, gross deletions, missense mutations, nonsense mutations and small insertions or deletions (resulting in frameshifts) of GATA3 have been reported in human HDR syndrome [2,4,5,[11][12][13][14][15][16], and thus haploinsufficiency of GATA3 is the mechanism of HDR syndrome [11].…”
mentioning
confidence: 99%
“…All four fully affected subjects had similar patterns of sensorineural deafness on audiography. A Japanese girl showing an association of hypoparathyroidism, sensorineural deafness and renal dysplasia has also been documented ( 14). Intravenous pyelography in this patient revealed aplasia of the right kidney and pelvocalyceal deformity of the left kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Renal dysplasia was observed only in the original patient. Aplasia of the right kidney was similar to those reported by Hasegawa et al (14) and Yumita et al (15). Thus, it is suggested that the clinical features of sensorineural deafness and renal abnormalities were not identical in the four previous reports and in our case study.…”
Section: Discussionmentioning
confidence: 99%